Smart governance as a new strategy on Jambi city policy innovations - Rio Yusri Maulan; Ovie Yanti; Nur Sukmawat (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The goal of the smart governance concept is modern urban management using state-of-the-art technologies, considering the applicable ecological standards while saving resources and achieving the expected results. In line with this, the government needs to build integrated ICTs services. Therefore, the government of Indonesia has legalized a regulation relating to smart city policy. In 2017, Indonesia introduce The Movement Towards 100 Smart Cities. The program aims to guide local government to further maximize the use of technology, both in improving public services and transformation of existing resources in local government to become more digital-based.This article uses a qualitative descriptive approach through out in-depth interviews, documentation and secondary data exploration to present the extent of the development of smart governance in Jambi City, Indonesia which explained driving factors (and challenges) to policy implementation in local government, although the process of digitization has been in right direction so far, improvement is needed in terms of enhancing digital resources, adjusting to the organizational culture, and implementing a more diverse collaboration strategy.